Training of Red Devil Fish (Amphilophus labiatus) Processing into Catfish Feed at Kedisan Village, Bangli, Bali - Fahrudin, Danil Eka; Afifah, Nur; Rahmadi, Imam; Arum, Antonia Nesa Sekar; Rahmawati, Irma; Khirania, Rosyana Putri; Banna, Muhammad Yasiqy Haidar; Safrillah, M. Rizky Eka Putra Vi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Kepulauan Riau (JPPM Kepri), 2025)
The Red Devil is an invasive freshwater fish. As a result of the presence of that fish, fish harvests in Kedisan Village have been decreased due to cultivated fish being preyed upon by Red Devil Fish. This workshop provided education and practice of repurposing red devil fish into catfish feed at Kedisan Village based on rural community problems. It measured the satisfaction index rate by the participants. Based on the implementation of activities to make catfish feed from red devil fish, it can be seen that red devils can be processed into catfish feed by adding additional ingredients. In addition, the socialization activities that have been implemented can be categorized as successful because of the high level of satisfaction from the participants.